RETARDED PALEA1 Controls Palea Development and Floral Zygomorphy in Rice - Yuan, Zheng (American Society of Plant Biologists, 2009)
Poaceae, one of the largest flowering plant families in angiosperms, evolved distinct inflorescence and flower morphology diverging from eudicots and other monocots. However, the mechanism underlying the specification of flower morphology in grasses remains unclear. Here we show that floral zygomorphy along the lemma-palea axis in rice (Oryza sativa) is partially or indirectly determined by the CYCLOIDEA (CYC)-like homolog RETARDED PALEA1 (REP1), which regulates palea identity and development. The REP1 gene is only expressed in palea primordium during early flower development, but during later floral stages is radially dispersed in stamens and the vascular bundles of the lemma and palea. The development of palea is significantly retarded in the rep1 mutant and its palea has five vascular bundles, which is similar to the vascular pattern of the wild-type lemma. Furthermore, ectopic expression of REP1 caused the asymmetrical overdifferentiation of the palea cells, altering their floral asymmetry. This work therefore extends the function of the TCP gene family members in defining the diversification of floral morphology in grasses and suggests that a common conserved mechanism controlling floral zygomorphy by CYC-like genes exists in both eudicots and the grasses.